Data retrieval from library systems based on the open systems model - CORNISH, Alan (Information technology and libraries, 2001)
An important advantage of relational, structured query language (SQL)-compliant databases is described: they enable a library to employ standard report-building software to retrieve data from multiple data sources. The ability of a library's integrated library system and other major systems to support this type of data retrieval is of critical importance. Two SQL reporting tools, Cognos Impromptu and Seagate Crystal Reports, are briefly discussed.